Effective grain potential in a plasma with external sources of ionization - Zagorodny, A.G.; Filippov, A.V.; Pal’, A.F.; Starostin, A.N.; Momot, A.I. (Вопросы атомной науки и техники, 2006)
A new approach is proposed for analytical description of effective grain potentials in dusty plasmas. The basic idea is to describe absorption of electrons and ions by grain in terms of effective point sinks introduced into the equations of plasma dynamics. The proposed approach makes it possible to find explicit relations for the potential and particle densities distributions. The example of grain screening is considered for the case of weakly ionized plasma in the presence of the external sources of plasma ionization.